2019
DOI: 10.1101/530386
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

BalticMethanosarcinaandClostridiumcompete for electrons from metallic iron

Abstract: 13Microbial induced corrosion of steel structures, used for transport or storage of fuels, 14 chemical weapons or waste radionuclides, is an environmental and economic threat. 15In non-sulfidic environments, the exact role of methanogens in steel corrosion is 16 poorly understood. From the non-sulfidic, methanogenic sediments of the Baltic Sea 17 corrosive communities were enriched using exclusively Fe 0 as electron donor and 18 CO 2 as electron acceptor. Methane and acetate production were persistent for thre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
(83 reference statements)
0
2
0
Order By: Relevance
“…Figure 9. Estimated commensual interaction between Fe 0chordinator Clostridium-acetogen and acetate-utilized Methanosarcina-methanogen: 1a direct mechanism of electron absorption; 2an absorption mechanism based on abiotic H2 [7] Thus, in the study [8] direct absorption of electron from Fe 0 for Methanobacterium strain IM1, because:…”
Section: Resultsmentioning
confidence: 99%
“…Figure 9. Estimated commensual interaction between Fe 0chordinator Clostridium-acetogen and acetate-utilized Methanosarcina-methanogen: 1a direct mechanism of electron absorption; 2an absorption mechanism based on abiotic H2 [7] Thus, in the study [8] direct absorption of electron from Fe 0 for Methanobacterium strain IM1, because:…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Yee et al (83) showed the ability of Methanosarcina species to directly accept electrons from insoluble electron donors, including conductive particles and biocathodes that show similarities to the metal sheet piles in our study. A study by Jaramillo et al (84) observed a competition of Methanosarcina species with acetogens in nonsulfidic environments. The study's observations of higher methanogenesis rates without a mixed community that includes Clostridiales indicated a competition to obtain electrons from elemental iron.…”
Section: Figmentioning
confidence: 99%